China's Foreign Aid to Countries in Southeast Asia During The Covid-19 Pandemic Massa - Risalatu Mirajiah (International Journal of Education, Information Technology, and Others, 2022)
China is the country that has provided the most assistance during the Covid-19 pandemic to countries in the Southeast Asian Region. Some concrete efforts have been made by China such as diplomacy of masks, vaccines, and Medical Equipment and Personal Protective Equipment (PPE) against all countries in the Southeast Asian region, including Indonesia, Laos, Cambodia and Myanmar. These countries believe that China's humanitarian assistance is very much needed in this Covid-19 pandemic situation. However, in the course of this series of efforts, it gave rise to speculative assumptions from the international community. So that in the end, from this paper the author tries to answer the question of what is behind China's efforts to make foreign aid efforts to countries in the Southeast Asian Region using the concept of foreign aid from Maria Andersson. Maria explained that there are humanitarian, economic and socio-political motives in influencing a country's foreign aid. This is what the author will explain in this paper, in an effort to answer questions related to China's background in expanding its humanitarian assistance in the Southeast Asian Region. It is hoped that this paper can be used as a comparative material for similar research and as a contribution to ideas for interested parties.